Diagnosis and treatment of gastric foreign body (earrings) case in a cat - Polat, Eren (Univ Cordoba, 2022)
In this study, information was given about the diagnosis and treatment of a 2-month-old female cat that was admitted to the clinic with the complaint of swallowing a foreign body (earring). The medical history of the case indicated that the cat had a good appetite and defecated normally. Abdominal palpation showed a distended stomach. No clinical findings other than the distended stomach were noted during clinical examination. Radiographic examination revealed a foreign body with hyperechoic contrast in the stomach. Due to the presence of a penetrating foreign body, it was decided to urgently perform an operation. For the operation, the cat was anesthetized with xylazine and ketamine. The foreign body (earring) in the stomach was removed from the body by gastrotomy. Special diet and parenteral antibiotics were applied to the patient in the postoperative period. During the interviews with the owner on the 15th postoperative day, it was learned that the cat continued its normal life.
Keywords: Cat; earring; foreign body; gastrotomy